2011
DOI: 10.1007/s11134-011-9227-0
|View full text |Cite
|
Sign up to set email alerts
|

Tail asymptotics for a generalized two-demand queueing model—a kernel method

Abstract: In this paper, we consider a generalized two-demand queueing model, the same model studied in Wright (Adv. Appl. Prob., 24, 986-1007, 1992). Using this model, we show how the kernel method can be applied to a two-dimensional queueing system for exact tail asymptotics in the stationary joint distribution and also in the two marginal distributions. We demonstrate in detail how to locate the dominant singularity and how to determine the detailed behavior of the unknown generating function around the dominant sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 24 publications
(39 reference statements)
2
45
0
Order By: Relevance
“…This method can also be used to get exact asymptotics, but it has been limited to relatively simple models such as tandem or parallel queues (e.g., see Flatto and McKean 1977). Its recent studies can be found in Guillemin and van Leeuwaarden (2011) and Li and Zhao (2010), where the approach is called a kernel method.…”
Section: A Methods Using Riemann Surfacementioning
confidence: 99%
“…This method can also be used to get exact asymptotics, but it has been limited to relatively simple models such as tandem or parallel queues (e.g., see Flatto and McKean 1977). Its recent studies can be found in Guillemin and van Leeuwaarden (2011) and Li and Zhao (2010), where the approach is called a kernel method.…”
Section: A Methods Using Riemann Surfacementioning
confidence: 99%
“…This analytic approach is called the kernel method (see, e.g. [18], [23], and [26]). In the kernel method, the generating function is more convenient to use than the moment generating function.…”
Section: Definitionmentioning
confidence: 99%
“…In recent years this classical approach has been renewed in combination with other methods (see, e.g. [18] and [23]). However, its application is limited to skip-free processes because of technical reasons (see Remark 3).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we applied the kernel method to investigate exact tail asymptotic properties of the joint stationary probabilities and the marginal distribution of the fluid queue driven by an M/M/c queue. Different from the model studied in [11] and [10], for which tail asymptotic properties are symmetric between the level and the phase, since both level and phase processes are discrete, the tail asymptotics for φ c−1 (α) and ψ(z) are asymmetric in this paper, since the phase process is discrete and level process is continuous.…”
Section: Discussionmentioning
confidence: 73%